People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. They are walking on Almaden Boulevard and are crossing West San Fernando Street in a crosswalk. Some of the people are wearing tee shirts that read: "Walk for women. YWCA 1986" and some are carrying balloons. There are barricades up on West San Fernando Street possible indicating that the street is closed off. A sign is visible on the building in the background on the left that reads: "Union B[ank]" and a sign rising from the roof of the tall white building in the background that reads: "Hotel DeAnza."